A Rare Case of Isolated Cystic Hydatid of Thyroid Gland. Issue 10 (March 2016) - Eken, Huseyin; Isik, Arda; Balci, Gulhan; Firat, Deniz; Cimen, Orhan; Soyturk, Mehmet
Abstract : Abstract: Hydatid cysts are most frequently localized within the liver and lungs, although they can also be found in highly vascularized tissues such as the brain, muscle, heart, pancreas, adrenal, and thyroid glands. A 65-year-old female patient was admitted to our clinic with complaints of a progressively growing mass that was compressing the surrounding tissues and causing respiratory distress. The pathological result was obtained as cytic hydatid. In patients with diagnosed hydatid cysts in the liver, systemic evaluation is necessary to rule out involvement of other organs. Among patients presenting with growths located in the neck, primary hydatid cyst of the thyroid gland must be considered in endemic regions.